Targeting Natural Killer Cells for Improved Immunity and Control of the Adaptive Immune Response - Pierce, Stephen; Geanes, Eric S.; Bradley, Todd (Frontiers in Cellular and Infection Microbiology, 2020)
Natural killer (NK) cells are critical for targeting and killing tumor, virus-infected and stressed cells as a member of the innate immune system. Recently, NK cells have also emerged as key regulators of adaptive immunity and have become a prominent therapeutic target for cancer immunotherapy and infection control. NK cells display a diverse array of phenotypes and function. Determining how NK cells develop and are regulated is critical for understanding their role in both innate and adaptive immunity. In this review we discuss current research approaches into NK cell adaptive immunity and how these cells are being harnessed for improving cancer and vaccination outcomes.